Degradação de efluente têxtil sintético utilizando os processos oxidativos avançados foto-fenton artificial e foto-fenton solar - França, Aline Aparecida Carvalho (2021)
The present work aimed to evaluate the efficiency of the photo- Fenton process assisted by artificial or solar light applied in the treatment of synthetic textile effluent. For the study of solar radiation was designed and built a solar reactor type Compound Parabolic Collector (CPC), and the efficiency of the treatment was analyzed in terms of color removal, chemical oxygen demand (COD) and spectral scanning of samples. The results obtained showed that the photo-Fenton process was efficient in discoloring the effluent, with emphasis to the study conducted by sunlight that in all operational conditions of work presented removal rates above 90%. In terms of COD, the best efficiency was obtained when 1250 mg L-1 e :62,5 mg L-1 showing rates of 85.40% and 50.20% for the process with artificial or solar light respectively.